2021
DOI: 10.1111/hdi.12952
|View full text |Cite
|
Sign up to set email alerts
|

Sodium and ultrafiltration profiling in hemodialysis: A long‐forgotten issue revisited

Abstract: Sodium and ultrafiltration profiling are method of dialysis in which dialysate sodium concentration and ultrafiltration rate are altered during the course of the dialysis session. Sodium and ultrafiltration profiling have been used, commonly simultaneously, to improve hemodynamic stability during hemodialysis. Sodium profiling is particularly effective in decreasing the incidence of intradialytic hypotension, while ultrafiltration profiling is suggested to decrease subclinical repeated end organ ischemia durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
(138 reference statements)
0
5
0
Order By: Relevance
“…In recent years, with the development of science and technology, some personalized biofeedback systems with real-time online monitoring equipment began to appear in the field of dialysis. Blood volume biofeedback, body temperature biofeedback, blood pressure biofeedback, sodium concentration biofeedback [26] are the most commonly used clinical applications. The biofeedback system of blood volume is suitable for volume management of patients with hypotension tendency and significant weight gain during dialysis.…”
Section: Biofeedback Systemmentioning
confidence: 99%
“…In recent years, with the development of science and technology, some personalized biofeedback systems with real-time online monitoring equipment began to appear in the field of dialysis. Blood volume biofeedback, body temperature biofeedback, blood pressure biofeedback, sodium concentration biofeedback [26] are the most commonly used clinical applications. The biofeedback system of blood volume is suitable for volume management of patients with hypotension tendency and significant weight gain during dialysis.…”
Section: Biofeedback Systemmentioning
confidence: 99%
“…Many publications have reported that dialysate sodium profiling improves tolerance to dialysis session. However, sodium profiling is most commonly associated with chronic overload due to increased average dialysate sodium, which is why its routine use to limit or prevent intradialytic hypotension is associated with increased weight gain 22 and higher all‐cause mortality 23 . Therefore, it has been claimed that “isonatric hemodialysis should be pursued, but sodium profiling, for the most part, avoided.” 24 …”
Section: Rationalementioning
confidence: 99%
“…Besides, it prevents more hypotension during HD by maintaining intravascular volume [ 19 ]. Recent studies have advocated the combination of the UF and sodium profiles to reduce numerous complications arising in HD [ 19 , 20 ]. For example, the linear UF-sodium profiling had improved BP in the HD patients in one study by Borzou et al (2015) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%